2018
DOI: 10.1371/journal.pgen.1007785
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic variants influence on the placenta regulatory landscape

Abstract: From genomic association studies, quantitative trait loci analysis, and epigenomic mapping, it is evident that significant efforts are necessary to define genetic-epigenetic interactions and understand their role in disease susceptibility and progression. For this reason, an analysis of the effects of genetic variation on gene expression and DNA methylation in human placentas at high resolution and whole-genome coverage will have multiple mechanistic and practical implications. By producing and analyzing DNA s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 79 publications
(102 reference statements)
1
52
0
Order By: Relevance
“…Several studies have shown that candidate loci associated with placenta-specific maternal methylation are associated with actual parental allelic transcriptional bias at only half the loci [6, 13, 14]. Additionally, allelic imbalances in DNA methylation may reflect the underlying differences in primary DNA sequence [47, 48]. Concerning RNA-Seq-based studies, spurious claims of parental monoallelic expression may arise from modest informative sample sets, random sampling errors of transcript pools entering library preparation and RNA-sequencing, insufficient read coverage and limited QC (e.g., RNA-Seq mapping or genotyping errors), and loose statistical criteria in defining imprinted genes (reviewed in [7]).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that candidate loci associated with placenta-specific maternal methylation are associated with actual parental allelic transcriptional bias at only half the loci [6, 13, 14]. Additionally, allelic imbalances in DNA methylation may reflect the underlying differences in primary DNA sequence [47, 48]. Concerning RNA-Seq-based studies, spurious claims of parental monoallelic expression may arise from modest informative sample sets, random sampling errors of transcript pools entering library preparation and RNA-sequencing, insufficient read coverage and limited QC (e.g., RNA-Seq mapping or genotyping errors), and loose statistical criteria in defining imprinted genes (reviewed in [7]).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated how genetic variation affects gene expression (Banovich et al, 2018;Delahaye et al, 2018). Kilpinen et al (2013) suggest that genetic variation appears to be the primary driver of gene expression variation.…”
Section: Introductionmentioning
confidence: 99%
“…An integrative analysis using combinations of genomic, epigenomic, and transcriptomic data will provide a basis for biomarker discovery and help to provide insight of disease etiology. Genomic sequence variation, epigenetic factor, and gene expression are interdependent and jointly contribute to the normal functioning or dysfunction of tissue (Delahaye et al, 2018). For example, the sequencing variations can alter the TF binding strength to regulate gene expression directly (Karczewski et al, 2011;Madsen et al, 2018;Johnston et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…b PlaNET utilizes a subset of ethnicity-predictive sites from the HM450K. To investigate whether genetic signal is present in the measurement for these sites, we cross-referenced ethnicity-predictive sites to an existing placental mQTL database [42] and determined whether any sites had SNPs present in either the probe body, CpG site of interrogation, or single base extension sites, based on dbSNP137…”
Section: Resultsmentioning
confidence: 99%